Neuroprotective Effects of Tryptanthrin-6-Oxime in a Rat Model of Transient Focal Cerebral Ischemia; Pharmaceuticals; Vol. 16, iss. 8 - Plotnikov M. B. Mark Borisovich; Chernysheva G. A. Galina Anatoljevna; Smolyakova V. I. Vera Ivanovna; Aliev O. I. Oleg Ibragimovich; Anishchenko A. M.; Ulyakhina O. A.; Anfinogenova N. D. Nina Dzhonovna; Osipenko A. N.; Kovrizhina A. R. Anastasia Ruslanovna; Khlebnikov A. I. Andrey Ivanovich; Drozd A. G. Anastasiya Gennadjevna; Plotnikov E. V. Evgeny Vladimirovich (2023, 2023)
Title screen